2008
DOI: 10.3167/sa.2008.520207
|View full text |Cite
|
Sign up to set email alerts
|

Military Occupation as Carceral Society: Prisons, Checkpoints, and Walls in the Israeli-Palestinian Struggle

Abstract: Palestinians in the Occupied Territories have been subject to increasing confinement, starting with prisons in the 1970s and 1980s and growing into a regime of checkpoints and walls that encircle entire towns and villages. After a historical review of the incremental stages of this incarceration, the article examines the overall impact of prisons, checkpoints, and walls, based on observations garnered from more than a dozen research trips over two decades and a review of research by others. Although these arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Beyond harsh implications for the occupied society, prolonged occupation usually comes with heavy material costs for the occupying society, as well as unfavorable consequences for its collective identity (Bar-Tal & Schnell, 2013b;Bornstein, 2008;Rosler et al, 2009). Previous studies suggested that societies tend to morally disengage from their past or currently unacceptable wrongdoing (Bandura, 1999;Coman et al, 2014) thus minimizing its perceived negative consequences (Leidner et al, 2010) and reducing moral emotions (Lickel et al, 2011;Wohl & Branscombe, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond harsh implications for the occupied society, prolonged occupation usually comes with heavy material costs for the occupying society, as well as unfavorable consequences for its collective identity (Bar-Tal & Schnell, 2013b;Bornstein, 2008;Rosler et al, 2009). Previous studies suggested that societies tend to morally disengage from their past or currently unacceptable wrongdoing (Bandura, 1999;Coman et al, 2014) thus minimizing its perceived negative consequences (Leidner et al, 2010) and reducing moral emotions (Lickel et al, 2011;Wohl & Branscombe, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In doing so, it provides us with unique insight into a centerpiece of the Israeli‐Palestinian conflict, which remains grossly understudied due to issues of identification. In the West Bank, it is almost impossible to distinguish one facet of control from others; as a result, existing studies of checkpoints have been unsystematic and incomplete (Brown ; Bornstein ; Kotef and Amir ; Naaman ), with econometric reports going so far as to claim that “the losses of internal closures are difficult to measure” (Aranki , 28) or that “quantifying the economic impact of current restrictions is difficult given the paucity of data” (World Bank , 1)…”
mentioning
confidence: 99%
“…Yet, we cannot ignore the possibility that any changes as a result of military occupations are often met with resistance, including guerrilla warfare, along with significant resistance from the general population by disobeying laws and restrictions put into place by the occupier (Bazargan, ). For example, in the first Palestinian Intifada, resistance by the people included the boycott of Israeli goods, refusal to pay taxes, the closing of shops, and resignations from government jobs (Bornstein, ).…”
Section: Related Literaturementioning
confidence: 99%